Asbestos Litigation in Madison County, Illinois: The Challenge Ahead - Victor E. Schwartz; Mark A. Behrens; Kimberly D. Sandner (Washington University Journal of Law & Policy, 2004)
Why is Madison County attracting so many claims and so much attention? What makes the lawsuit industry different there compared to other jurisdictions? We do not think the county’s reputation is the fault of jurors. In many cases, jurors are simply making judgments based on the evidence they are permitted to hear and the instructions they are given. As the St. Louis Post-Dispatch has said: “It’s a little hard to blame Madison County juries, since [cases] rarely come to trial. They’re normally settled. Instead, we wonder about the judges.” Similar concerns have been raised with respect to the Madison County Circuit Court’s handling of serious personal injury cases, such as asbestos-exposure suits. We understand that the judges in Madison County work hard, and we believe they mean well. They may view their role as helping to facilitate the resolution of claims on behalf of legitimately injured plaintiffs. For example, they may believe it is appropriate to handle asbestos cases from around the United States because asbestos litigation is national in scope. Nevertheless, it seems that the drive for efficiency is being promoted over basic fairness. It also appears that procedures adopted by the court to manage its large docket have simply invited the filing of more claims. In this Article, we will touch on some of the issues. We will then focus on asbestos litigation in Madison County, and suggest ways the asbestos litigation environment in the county should be improved and made fairer.
Keywords: Asbestos – Lawsuits & amp; claims; Class actions (Civil procedure); Mass torts; Torts – Law & amp; legislation – Illinois